Ho Chi Minh’s ideology on lifestyle and the construction of a new lifestyle for the youth of Ho Chi Minh City (Revista de Investigaciones Universidad del Quindío, 2021)
Ho Chi Minh (1890 - 1969) was not only a genius leader of the Vietnamese nation but also a great cultural figure of the world. Throughout his life, Ho Chi Minh has left many precious ideas for the Vietnamese people and humanity, especially the ideology of lifestyle.His ideology covers a wide range of aspects including working style, manners; education and learning; training ethics of each individual in the society. It is also these views that have contributed to clarify and orient the views on the new way of life of the Party and the State that Vietnam is building for the entire people of Vietnam.
Keywords: Ho Chi Minh; lifestyle; living style; working style; behavior; education; learning; ethics